Major Stress Sources Amongst Dental Students at Damascus University, Syria - Muhammad Rami Shehada; Ghaith Alfakhry; Issam Jamous; Abeer A. Aljoujou; Mahmoud Abdul_hak (Elsevier, 2023)
Introduction: Stress amongst dental students is frequently reported. Various environmental, socioeconomic, and cultural factors affect students' perceived stress levels. The aim of this study was to investigate stress levels and sources amongst undergraduate dental students at Damascus University, Syria. Methods: A cross-sectional design was used. A questionnaire was undertaken in 2019 at the Faculty of Dentistry at Damascus University. Students participated voluntarily in the survey. The sample comprised students at the preclinical and clinical stage. A modified 29-item version of the validated Dental Environmental Stress (DES) questionnaire with a 5-point scale (1 = not stressful to 5 = extremely stressful) was used as the measurement tool. Ethical approval was granted by Damascus University. Results: In all, 365 students participated in the study, with a response rate of 96% (365/379). Cronbach's alpha was 0.83, indicating good reliability of the measurement tool. The overall mean score of the perceived stress was 2.64 (95% confidence interval [CI], 2.5-2.7). The mean scores for clinical factors, academic work, educational environment, personal factors, and living accommodation were 3.22 (95% CI, 3.1-3.3), 3.17 (95% CI, 3.1-3.2), 2.99 (95% CI, 2.9-3.0), 2.15 (95% CI, 2.1-2.2), 2.15 (95% CI, 2.0-2.2), respectively. The specific stressors with the highest mean scores were lack of dental equipment and difficulty in finding requested clinical cases; the respective means were 4.1 (95% CI, 4.0-4.2) and 3.9 (95% CI, 3.8-4.0). Conclusions: The findings revealed moderate stress levels amongst students. The major stress factors pertained to stressors from the clinical, academic, and educational environment domains. Certain clinical and environmental stressors, such as difficulty in finding clinical cases and lack of dental equipment, were more powerful than the strongest academic stressors, such as examinations and grades and amount of assigned work.